PENGARUH LATIHAN INTERVAL SPRINT TERHADAP KECEPATAN LARI PADA SSB SIMPATIG U-15 - Reza Habibie; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstact: The problem in this research is that it often does not hit when chasing a fast ball, always loses as a result of winning the ball, is not fast when taking a fast ball, with such circumstances the ball originally score against the goal of the opponent, so it is difficult and less likely to score points. The title of this research is